EFFECT OF MULTIPLE TAXATIONS ON SMES GROWTH IN AKWA IBOM STATE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The study examined the effect of multiple taxations on smes growth in akwa ibom state. In order to carry out this study,specified research objectives were drawn from which null hypotheses were formulated and used for the study. The research designfor this study is a survey design. The population of the study consisted of all SMEs operators in Uyo urban. Simple randomsampling technique was used to select 398 respondents out of the population. The instrument used for data collection wasquestionnaire. Data from completed questionnaires was subjected to independent t-test analysis. The findings showed that effect of multiple taxations on the performance of SMEs in Uyo Urban. From all literatures reviewed, the researchers deduced that the development and operation of SMEs has economic impact on the nation.The study recommended that all SMEs should endeavor to pay their taxes as at when due. This should be done by Government providing enabling environment for them to operate and see it as one of the benefit accrued to such payment of taxes to the Government. Also Government should adequately createawareness on the need for SMEs to pay their taxes appropriately. Government should consider increasing tax incentives andexemptions as this will not only attract investors who are potential tax payers, it will encourage voluntary compliance andultimately leads to expansion of existing business interests of the SMEs in Akwa Ibom State as well as Nigeria as a whole. If theseare done all SMEs will willingly pay their taxes as at when due.